Improving English oral communication through multimodal learning strategies for secondary school students - Aya Ragab; Nur Arifah Drajati; Eka Bhudi Eka Bhudi Santosa (Universitas Negeri Semarang, 2025)
This report presents a conceptual framework for a multimodal learning platform designed to address critical educational needs in the 21st century: cultivating English speaking proficiency and instilling ethical digital citizenship. The proposed framework integrates visual, auditory, reading/writing, and kinesthetic instructional methods to create an engaging and inclusive learning environment. By leveraging the power of multimodal artificial intelligence (AI), the platform offers personalized, real-time feedback that promotes language acquisition and encourages responsible digital behavior. The framework is specifically tailored to the unique challenges and opportunities of the Indonesian educational context, aligning with national policies such as the Merdeka curriculum, while providing strategies to address issues of digital access and teacher professional development. The findings indicate that such an integrated, technology-driven approach can significantly enhance learning outcomes and prepare students to become informed, responsible, and effective global citizens.